The measurement of capabilities - Paul Anand; Cristina Santos; Ron Smith (The Open University, Economics Department, 2007)
It has often been claimed that it is impossible to measure human capabilities but within the methodological conventions of household survey design, we show that some non-financial capability indicators do already exist and we demonstrate how similar indicators, covering a wide range of life domains, can be constructed. This chapter draws on a continuing research project which contributes to the operationalisation of the capabilities approach by devising over 60 capability indicators which can be used to extend coverage of indices such as HDI, illustrating different ways in which such indicators may be analysed, and discussing some of the associated methodological issues that have emerged in the process. Based on usable observations from a national UK sample of 1000 adults, we use latent class analysis to identify an impoverished group of respondents with low capabilities across the board, build models of experienced violence and subjective wellbeing as a function of experienced and anticipated violence, and explore the relationship between capability indicators and subjective wellbeing. Substantive findings include: the identification of a group with low all round capabilities associated with low health and low income; evidence that fear of future violence can be a more significant determinant of subjective wellbeing than past experience of violence; and evidence which supports the view that a large diverse set of non-financial dimensions of capability have a detectable impact on subjective wellbeing. We conclude by discussing some of the econometric issues that have emerged in the course of this work.
Keywords: D60; C80; 330; capabilities; measurement; performance indicators; human development; welfare; economic statistics; freedom; happiness; subjective wellbeing; personality; gender differences; violence; causality; poverty; health; latent class analysis; Soziale Gerechtigkeit; Zufriedenheit; Sozialer Indikator; Wohlfahrtstheorie